Preparation process of high-conductivity composite cable material

By using copper, nickel oxide, titanium diboride and other materials, combined with high-temperature thermal shock sintering method with Joule heating principle, a high-conductivity composite cable material was prepared, which solved the problem of significant increase in the resistance of existing cable materials at high temperatures, and achieved the realization of Low resistance and high conductivity at high temperatures.

CN119419004APending Publication Date: 2025-02-11OPTA POLYMER JIANGSU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475284.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing cable materials are difficult to maintain low resistance at high temperatures, resulting in increased energy loss and cannot meet the needs of various fields.

Method used

Highly conductive composite cable material is prepared by using copper, nickel oxide, titanium diboride and other materials, through two ball milling and three sintering processes, combined with the high-temperature thermal shock sintering principle of Joule heating.

Benefits of technology

Maintain low resistance at high temperatures, reduce energy losses, improve conductivity, and extend the material's oxidation resistance temperature.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of cable materials, and discloses a preparation process of a high-conductivity composite cable material. The preparation process disclosed by the invention comprises the following steps: carrying out two times of ball milling and three times of sintering to obtain the high-conductivity composite cable material with oxidation resistance. The sintering process comprises a high-temperature thermal shock sintering mode based on the Joule heating principle. In view of the problem that the current cable material is difficult to keep low resistance at high temperature, the invention aims to provide the preparation process of the high-conductivity composite cable material, so that the cable can be used at high temperature, is not easy to oxidize, keeps low resistance and has an efficient conductive effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to a preparation process of a high-conductivity composite cable material. Background Art

[0002] Wires and cables are wire products used to transmit electrical energy, mainly including conductors and insulation layers. Wires are materials used for conducting electricity. The lower the resistance of the wire, the higher the conductivity, the higher the efficiency of transmitting electrical energy, and the better it can reduce energy loss during the transportation of electrical energy. Copper is often used as the main material for conductors due to its lower resistance.

[0003] Although copper has a low resistance, at high temperatures, its resistance will increase significantly as the temperature rises, resulting in greater losses when the cable transmits electrical energy under high temperature conditions, greatly reducing energy utilization. Reducing energy loss is a very important issue. Therefore, it is necessary to develop cable materials that can maintain low resistance at high temperatures to make cables. Although other raw materials are added to copper to make alloy materials in the prior art, the resistance of such alloy materials at high temperatures is still high and it is difficult to meet the needs of various fields. Therefore, there is still much room for improvement in the main materials of cables and they have broad application prospects. Summary of the invention

[0004] In view of the problem that current cable materials are difficult to maintain low resistance at high temperatures, the present invention aims to provide a preparation process for a highly conductive composite cable material.

[0005] The purpose of the present invention is to provide a preparation process of a high-conductivity composite cable material, the preparation process comprising: two ball milling and three sintering processes to obtain a high-conductivity composite cable material; the sintering process includes a high-temperature thermal shock sintering method based on the Joule heating principle.

[0006] The preparation process specifically comprises the following steps:

[0007] (1) Take the following components by mass: 80-100 parts of copper, 10-15 parts of titanium diboride, 7-12 parts of ferrosoferric oxide, 4-8 parts of magnesium oxide, and 12-20 parts of nickel oxide;

[0008] (2) Firstly, magnesium oxide, ferroferric oxide and titanium diboride are subjected to ball milling and mixing treatment to obtain ball mill A, and at the same time, copper and nickel oxide are mixed and ball milled under the same conditions to obtain ball mill B; ball mill A is laid on an electrically heated substrate for high-temperature thermal shock sintering reaction, and sintered once; after the first sintering is completed, it is naturally cooled for 5 to 10 minutes, and the current value is increased for secondary sintering. After the second sintering is completed, it is cooled to room temperature, and ball mill B is added and mixed and ground, and sintered for a third time to obtain a composite metal liquid;

[0009] (3) The composite metal liquid is injected into the mold, and then the mold is placed in a ventilated environment at room temperature, cooled naturally, and demolded to obtain a high-conductivity composite cable material.

[0010] Furthermore, the particle size of the ball mill A and B in step (2) is controlled to be 1 to 10 mm.

[0011] Furthermore, the first, second and third sintering in step (2) are all carried out under a protective atmosphere, and the protective gas is argon or neon.

[0012] Furthermore, the pressures of the first, second and third sintering atmospheres are 1.2-1.5 MPa, 1.6-1.8 MPa and 1.9-2.1 MPa, respectively. The present invention better induces changes in the composite metal structure through gradient pressurization, improves the overall density of the composite cable material, and enhances the compactness of the conductive main component, which is conducive to the composite conductive material being difficult to be easily oxidized at a higher temperature, maintaining a lower resistance, and having a good conductive effect.

[0013] Furthermore, the ball milling treatment in step (2) is: using zirconium dioxide as the ball milling medium, and ball milling at 300-500 r / min for 2-5 hours.

[0014] Furthermore, in the first sintering of step (2), the DC current is set to 5-10A, the temperature is 400-550°C, and the holding time is 40-60s; the second sintering is set to 12-20, the temperature is set to 900-1100°C, and the holding time is 40-60s; the third sintering is set to 10-15A, the temperature is 1100-1300°C, and the holding time is 20-40min.

[0015] Compared with the prior art, the advantages of the present invention are:

[0016] The present invention adopts copper, nickel oxide and titanium diboride as main conductive materials, wherein the boron atomic planes and titanium atomic planes in the crystal structure of titanium diboride appear alternately to form a two-dimensional network structure, wherein B is covalently bonded to the other three Bs, and the extra electron forms a large π bond. This graphite-like boron atomic layered structure and Ti outer electrons determine that TiB2 has good electrical conductivity and metallic luster, and the oxidation resistance temperature in the air can reach 1000°C. When doped in iron source and magnesium source, it can provide the effect of "stabilizer". The iron source and magnesium source form an iron-magnesium composite material with strong reducing property due to high-temperature thermal shock sintering and cooling based on the Joule heating principle. Combined with the added titanium diboride, it can effectively prevent the oxidation of conductive materials such as copper due to temperature increase, thereby increasing resistance. DETAILED DESCRIPTION

[0017] The following is a specific embodiment of a preparation process of a high-conductivity composite cable material of the present invention. It is necessary to point out that the following examples are only used to explain the present invention in more detail, rather than to narrow the scope of protection of the present invention. After reading the present invention, improvements and adjustments made by professionals in the technical field without departing from the concept of the present invention are within the scope of protection claimed by the present invention.

[0018] A preparation process of a high-conductivity composite cable material comprises the following steps:

[0019] (1) Take the following components by mass: 80-100 parts of copper, 10-15 parts of titanium diboride, 7-12 parts of ferrosoferric oxide, 4-8 parts of magnesium oxide, and 12-20 parts of nickel oxide;

[0020] (2) First, magnesium oxide, ferroferric oxide and titanium diboride are subjected to ball milling and mixing treatment, zirconium dioxide is used as a ball milling medium, and ball milling is performed at 300-500 r / min for 2-5 hours to obtain ball mill A. At the same time, copper and nickel oxide are mixed and ball milled under the same conditions to obtain ball mill B; ball mill A is placed on an electric heating substrate for high-temperature thermal shock sintering reaction, the temperature of the first sintering is 400-550°C, the time of the first sintering is 40-60s, and the DC current is set to 5-10A; after the first sintering is completed, it is naturally cooled for 5-10 minutes, the current is increased to 12-20A for a second sintering time of 40-60s, the temperature of the second sintering is 900-1100°C, after the second sintering is completed, it is cooled to room temperature, ball mill B is added and mixed and ground for 1-3 hours, and a third sintering is performed at a current of 10-15A and a temperature of 1100-1300°C, and maintained for 20-40 minutes to obtain a composite metal liquid;

[0021] (3) The composite metal liquid is injected into the mold, and then the mold is placed in a ventilated environment at room temperature, cooled naturally, and demolded to obtain a high-conductivity composite cable material.

[0022] Wherein, the particle size of the ball abrasives A and B is controlled within the range of 1 to 10 mm.

[0023] Among them, the first, second and third sintering are all carried out under a protective atmosphere, and the protective gas is argon or neon.

[0024] Among them, the pressures of the primary, secondary and tertiary sintering atmospheres are 1.2-1.5MPa, 1.6-1.8MPa and 1.9-2.1MPa respectively.

[0025] Example 1

[0026] A preparation process of a high-conductivity composite cable material comprises the following steps:

[0027] (1) Take the following components by mass: 80 parts of copper, 10 parts of titanium diboride, 7 parts of ferrosoferric oxide, 4 parts of magnesium oxide, and 12 parts of nickel oxide;

[0028] (2) First, magnesium oxide, ferroferric oxide and titanium diboride are subjected to ball milling and mixing treatment, and zirconium dioxide is used as a ball milling medium, and ball milling is performed at 400r / min for 3h to obtain ball mill A. At the same time, copper and nickel oxide are mixed and ball milled under the same conditions to obtain ball mill B; ball mill A is laid on an electric heating substrate for high-temperature thermal shock sintering reaction, the temperature of the first sintering is 400-550°C, the time of the first sintering is 50s, and the DC current is set to 8A; after the first sintering is completed, it is naturally cooled for 6min, and the current is increased to 15A for a second sintering time of 50s, and the temperature of the second sintering is 1000°C. After the second sintering is completed, it is cooled to room temperature, ball mill B is added and mixed and ground for 2h, and a third sintering is performed at a current of 12A and a temperature of 1200°C, and maintained for 30min to obtain a composite metal liquid;

[0029] (3) The composite metal liquid is injected into the mold, and then the mold is placed in a ventilated environment at room temperature, cooled naturally, and demolded to obtain a high-conductivity composite cable material.

[0030] Wherein, the particle size of the ball abrasives A and B is controlled within the range of 1 to 10 mm.

[0031] Among them, the first, second and third sintering are all carried out under a protective atmosphere, and the protective gas is argon.

[0032] Among them, the pressures of the first, second and third sintering atmospheres are 1.2MPa, 1.6MPa and 1.9MPa respectively.

[0033] Example 2

[0034] A preparation process of a high-conductivity composite cable material comprises the following steps:

[0035] (1) Take the following components by mass: 100 parts of copper, 15 parts of titanium diboride, 12 parts of ferrosoferric oxide, 8 parts of magnesium oxide, and 20 parts of nickel oxide;

[0036] (2) First, magnesium oxide, ferroferric oxide and titanium diboride are subjected to ball milling and mixing treatment, and zirconium dioxide is used as a ball milling medium, and ball milling is performed at 400 r / min for 3 hours to obtain ball mill A. At the same time, copper and nickel oxide are mixed and ball milled under the same conditions to obtain ball mill B; ball mill A is placed on an electric heating substrate for high-temperature thermal shock sintering reaction, the temperature of the first sintering is 550°C, the time of the first sintering is 60 seconds, and the DC current is set to 6A; after the first sintering is completed, it is naturally cooled for 6 minutes, and the current is increased to 15A for a second sintering time of 50 seconds, and the temperature of the second sintering is 1000°C. After the second sintering is completed, it is cooled to room temperature, ball mill B is added and mixed and ground for 2 hours, and a third sintering is performed at a current of 12A and a temperature of 1200°C, and maintained for 30 minutes to obtain a composite metal liquid;

[0037] (3) The composite metal liquid is injected into the mold, and then the mold is placed in a ventilated environment at room temperature, cooled naturally, and demolded to obtain a high-conductivity composite cable material.

[0038] Wherein, the particle size of the ball abrasives A and B is controlled within the range of 1 to 10 mm.

[0039] Among them, the first, second and third sintering are all carried out under a protective atmosphere, and neon is used as the protective gas.

[0040] Among them, the pressures of the first, second and third sintering atmospheres are 1.2MPa, 1.6MPa and 1.9MPa respectively.

[0041] Example 3

[0042] A preparation process of a high-conductivity composite cable material comprises the following steps:

[0043] (1) Take the following components by mass: 90 parts of copper, 12 parts of titanium diboride, 10 parts of ferrosoferric oxide, 6 parts of magnesium oxide, and 15 parts of nickel oxide;

[0044] (2) First, magnesium oxide, ferroferric oxide and titanium diboride are subjected to ball milling and mixing treatment, and zirconium dioxide is used as a ball milling medium, and ball milling is performed at 400r / min for 3h to obtain ball mill A. At the same time, copper and nickel oxide are mixed and ball milled under the same conditions to obtain ball mill B; ball mill A is laid on an electric heating substrate for high-temperature thermal shock sintering reaction, the temperature of the first sintering is 500℃, the time of the first sintering is 50s, and the DC current is set to 6A; after the first sintering is completed, it is naturally cooled for 6min, and the current is increased to 15A for a second sintering time of 50s, and the temperature of the second sintering is 1000℃. After the second sintering is completed, it is cooled to room temperature, ball mill B is added and mixed and ground for 2h, and a third sintering is performed at a current of 12A and a temperature of 1200℃, and maintained for 30min to obtain a composite metal liquid;

[0045] (3) The composite metal liquid is injected into the mold, and then the mold is placed in a ventilated environment at room temperature, cooled naturally, and demolded to obtain a high-conductivity composite cable material.

[0046] Wherein, the particle size of the ball abrasives A and B is controlled within the range of 1 to 10 mm.

[0047] Among them, the first, second and third sintering are all carried out under a protective atmosphere, and neon is used as the protective gas.

[0048] Among them, the pressures of the first, second and third sintering atmospheres are 1.2MPa, 1.6MPa and 1.9MPa respectively.

[0049] Comparative Example 1: It is basically the same as Example 2, except that the first and second sintering are omitted and only the third sintering is retained.

[0050] Comparative Example 2: Based on Comparative Example 1, the ferrosoferric oxide and magnesium oxide components were removed.

[0051] Comparative Example 3: It is basically the same as Example 2, except that the atmosphere during the three sinterings is set to 1.2 MPa.

[0052] The composite cable material of each embodiment and comparative example is used to make a cross-sectional area of ​​1mm 2 , the length of the wire to be tested is 1m, and the resistance of the wire to be tested is tested by a multimeter at 20°C and 100°C respectively, and the resistivity is calculated. For each embodiment or comparative example, 10 wires to be tested are prepared, and the test data are averaged.

[0053] Table 1. Performance test results

[0054] Group 20℃ resistivity (Ω·m) 100℃ resistivity (Ω·m) Example 1 <![CDATA[1.733X10 -8 ]]> <![CDATA[1.782X10 -8 ]]> Example 2 <![CDATA[1.753X10 -8 ]]> <![CDATA[1.798X10 -8 ]]> Example 3 <![CDATA[1.746X10 -8 ]]> <![CDATA[1.789X10 -8 ]]> Comparative Example 1 <![CDATA[1.857X10 -8 ]]> <![CDATA[2.102X10 -8 ]]> Comparative Example 2 <![CDATA[1.916X10 -8 ]]> <![CDATA[2.143X10 -8 ]]> Comparative Example 3 <![CDATA[1.787X10 -8 ]]> <![CDATA[1.842X10 -8 ]]>

[0055] From the test results obtained in the embodiments and comparative examples, it can be seen that the resistivity obtained in embodiments 1 to 3 is lower than that in comparative examples 1 and 2 at the same temperature, and the conductive performance is better; comparative example 1 is basically the same as embodiment 2, except that the first and second sintering are missing, and only the third sintering is retained, resulting in the failure to add the iron-magnesium active material produced by the high-temperature thermal shock sintering based on the Joule heating principle, which increases the resistivity; comparative example 2 removes the ferroferric oxide and magnesium oxide components on the basis of comparative example 1, which further causes an increase in the resistivity; comparative example 3: is basically the same as embodiment 2, except that the atmosphere during the three sinterings is set to 1.2MPa, which leads to an increase in the resistivity. It can be seen that the pressure effect of the gradient increase helps to control the conductivity.

[0056] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A process for preparing a high-conductivity composite cable material, characterized in that: The preparation process includes: two ball milling and three sintering processes to obtain a high-conductivity composite cable material; the sintering process includes a high-temperature thermal shock sintering method based on the Joule heating principle.

2. The preparation process of the high-conductivity composite cable material according to claim 1, characterized in that: The preparation process specifically comprises the following steps: (1) Take the following components by mass: 80-100 parts of copper, 10-15 parts of titanium diboride, 7-12 parts of ferrosoferric oxide, 4-8 parts of magnesium oxide, and 12-20 parts of nickel oxide; (2) Firstly, magnesium oxide, ferroferric oxide and titanium diboride are subjected to ball milling and mixing treatment to obtain ball mill A, and at the same time, copper and nickel oxide are mixed and ball milled under the same conditions to obtain ball mill B; ball mill A is laid on an electrically heated substrate for high-temperature thermal shock sintering reaction, and sintered once; after the first sintering is completed, it is naturally cooled for 5 to 10 minutes, and the current value is increased for secondary sintering. After the second sintering is completed, it is cooled to room temperature, and ball mill B is added and mixed and ground, and sintered for a third time to obtain a composite metal liquid; (3) The composite metal liquid is injected into the mold, and then the mold is placed in a ventilated environment at room temperature, cooled naturally, and demolded to obtain a high-conductivity composite cable material.

3. The preparation process of the high-conductivity composite cable material according to claim 2, characterized in that: The particle size of the ball mills A and B in step (2) is controlled to be 1 to 10 mm.

4. The preparation process of the high-conductivity composite cable material according to claim 2, characterized in that: The first, second and third sintering in step (2) are all carried out under a protective atmosphere, and the protective gas is argon or neon.

5. The process for preparing a high-conductivity composite cable material according to claim 4, characterized in that: The pressures of the primary, secondary and tertiary sintering atmospheres are 1.2-1.5 MPa, 1.6-1.8 MPa and 1.9-2.1 MPa respectively.

6. The process for preparing the high-conductivity composite cable material according to claim 2, characterized in that: The ball milling treatment in step (2) is as follows: using zirconium dioxide as the ball milling medium, and ball milling at 300-500 r / min for 2-5 hours.

7. The process for preparing a high-conductivity composite cable material according to claim 1, characterized in that: In the step (2), the first sintering is performed by setting the DC current to 5-10A, the temperature to 400-550°C, and the holding time to 40-60s; the second sintering is performed by setting the DC current to 12-20, the temperature to 900-1100°C, and the holding time to 40-60s; the third sintering is performed by setting the DC current to 10-15A, the temperature to 1100-1300°C, and the holding time to 20-40min.